Repurposing sulfonamide-based antidiabetic agents against polycystic ovary syndrome: a molecular docking and dynamics simulation approach - Roney, Miah; Issahaku, Abdul Rashid; Hamim, S.M. Istiaque; Wilhelm, Anke; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age, marked by hyperinsulinemia, hyperandrogenism, menstrual irregularities, and long-term metabolic complications. Cytochrome P450 17A1 (CYP17A1) is a key enzyme in the biosynthesis of adrenal and gonadal steroids, and its overexpression leads to enhanced conversion of androgens into testosterone, contributing to hyperandrogenism. Targeting CYP17A1 activity presents a viable strategy to mitigate androgen production in the ovaries. In this study, sulfonamide-based antidiabetic drugs were evaluated through molecular docking to identify potential CYP17A1 inhibitors. Among the candidates, Chlorpropamide and Tolazamide demonstrated notable binding affinities and prime MM/GBSA energies of −5.04, −16.07 and −5.79, −14.90 kcal/mol, respectively, compared to the reference compound Clomiphene (–7.59, −14.62 kcal/mol). Molecular dynamics (MD) simulations further validated the enhanced stability of the Chlorpropamide and Tolazamide complexes over the apo form and the reference compound, supported by RMSD, RMSF, RoG, SASA, PCA, and DCCM analyses. Post-MD MM/GBSA binding energy calculations confirmed favorable interactions, with Chlorpropamide and Tolazamide showing −37.03±3.55 and −27.82±3.40 kcal/mol, respectively, while Clomiphene showed −45.16±5.96 kcal/mol. Furthermore, ADME profiling using SwissADME revealed that both Chlorpropamide and Tolazamide possess favorable pharmacokinetic and drug-likeness properties, including high gastrointestinal absorption, good bioavailability scores, and compliance with major drug-likeness filters, supporting their potential as viable therapeutic agents. These results highlight the potential of Chlorpropamide and Tolazamide as promising therapeutic agents for PCOS management.